The problematic allure of the binary in nursing theoretical discourse - Thorne, Sally E. (Nursing philosophy, 2004)
Recent ideological positioning on the world stage has born a startling resemblance to a form of positioning within nursing theory - that of taking complex ideas, reducing them to a simplistic binary form, and uncritically adopting one half of that form. In some cases, this adoption of a binary position has led to a passionately held form of ‘othering’ that prohibits a healthy and critical engagement with ideas. As alluring as settling for the binary form may be - we argue for holding binaries in tension as a catalyst for stimulating dialogue - reasoning and exploration of new ways of wrestling with the social and moral complexity of nursing.